Epidemiology, molecular epidemiology, and risk factors for renal cell carcinoma - Chiara Paglino; Ilaria Imarisio; Bruno Rovereto (Frontiers Media S.A., 2011)
Despite only accounting for approximately 2% of all new primary cancer cases, renal cell carcinoma (RCC) incidence has dramatically increased over time. Incidence rates vary greatly according to geographic areas, so that it is extremely likely that exogenous risk factors could play an important role in the development of this cancer. Several risk factors have been linked with RCC, including cigarette smoking, obesity, hypertension (and antihypertensive drugs), chronic kidney diseases (also dialysis and transplantation), as well as the use of certain analgesics. Furthermore, although RCC has not generally been considered an occupational cancer, several types of occupationally-derived exposures have been implicated in its pathogenesis. These include exposure to asbestos, chlorinated solvents, gasoline, diesel exhaust fumes, polycyclic aromatic hydrocarbons, printing inks and dyes, cadmium and lead. Finally, families with a predisposition to the development of renal neoplasms were identified and the genes involved discovered and characterized. Therefore, there are now four well-characterized, genetically determined syndromes associated with an increased incidence of kidney tumors, i.e., Von Hippel Lindau (VHL), Hereditary Papillary Renal Carcinoma (HPRC), Birt-Hogg-Dubé Syndrome (BHD), and Hereditary Leiomyomatosis and Renal Cell Cancer (HLRCC). This review will address present knowledge about the epidemiology, molecular epidemiology and risk factors of RCC.